2010
DOI: 10.1111/j.1440-1630.2009.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

A working reality: Evaluating enhanced intersectoral links in supported employment for people with psychiatric disabilities

Abstract: The study found that the enhanced intersectoral links approach was effective in achieving outcomes consistent with international studies of SE programmes and may offer a viable alternative to the co-location of employment specialists with community mental health teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
0
35
0
2
Order By: Relevance
“…Consistent with research conducted in other comparable Western countries, Australian and New Zealand studies have reported employment rates for people with SMI between 46% and 65% [6466]. In spite of these positive outcomes, the system still presents structural weaknesses leading to diminished quality and outcomes of the overall service.…”
Section: A Supported Employment Program In Australiamentioning
confidence: 55%
“…Consistent with research conducted in other comparable Western countries, Australian and New Zealand studies have reported employment rates for people with SMI between 46% and 65% [6466]. In spite of these positive outcomes, the system still presents structural weaknesses leading to diminished quality and outcomes of the overall service.…”
Section: A Supported Employment Program In Australiamentioning
confidence: 55%
“…Some studies found that clients with a lower level of psychopathology were more likely to attain employment (Regenold et al 1999;Sherring et al 2010). Similarly, clients with fewer recent psychiatric hospitalizations and fewer negative mental health symptoms were more likely to benefit from the SE program, as evidenced by higher rates of obtaining competitive employment and increased hours of work per month (Cook 2007).…”
Section: Intrinsic Characteristicsmentioning
confidence: 99%
“…; Waghorn, Childs et al ., ). The main challenge to this approach is attaining high fidelity to IPS principles (Bond, Peterson et al ., ; Sherring et al ., ). This is because organisational culture, policies, and practices of both agencies may need to change.…”
Section: Introductionmentioning
confidence: 97%
“…This is a different implementation approach to that previously reported (Killackey et al, 2008), and is achieved by establishing an evidence-based supported employment programme within a community mental health service Waghorn, Childs et al, 2012). The main challenge to this approach is attaining high fidelity to IPS principles (Bond, Peterson et al, 2012;Sherring et al, 2010). This is because organisational culture, policies, and practices of both agencies may need to change.…”
Section: Introductionmentioning
confidence: 99%